(3cTa GdeWGdHs - (3GdMfaj GdJjehQj, eMeO Hf CMeOs ((3YHO GdQMje QMej GHf eUWai CafOjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdTeS VjGA hGdbeQ efjQG deG SCdfj bQI Yjfj GdhdO GdCYR Cf CLeY QSGdI dg eajOI aj GdYed HGdQHY GdeLjH jchf faYgG ddRcj hGdHdjO Ydi GdShGA dCf CcKQ QSGFd Gdbhe Ydi GdGNJUGQ s
(3BNQgG (B:s
(3NGJeI aj GNJHGQ UMI GdQHY GdeLjH VY GdNjW Ydi eg OQLI aEf bWY GdNjW LejY eG hbY JMJg ef eQHY GdHjhJ eKdJG ef GdeQcR Edi BNQ GdbhS agh UMjM WQjb BNQ CfRd ef GdSJfjfj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf (B2\367s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3Gdadc hGdJfLje hGdejbGJs